2012
DOI: 10.1212/wnl.0b013e318253d54b
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance of GBA mutation carriers with early-onset PD

Abstract: Objective: To assess the cognitive phenotype of glucocerebrosidase (GBA) mutation carriers with early-onset Parkinson disease (PD). Methods:We administered a neuropsychological battery and the University of Pennsylvania Smell Identification Test (UPSIT) to participants in the CORE-PD study who were tested for mutations in PARKIN, LRRK2, and GBA. Participants included 33 GBA mutation carriers and 60 noncarriers of any genetic mutation. Primary analyses were performed on 26 GBA heterozygous mutation carriers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
221
5
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(248 citation statements)
references
References 29 publications
9
221
5
9
Order By: Relevance
“…Mutations in GBA are now recognized as an independent risk factor for development of cognitive impairment in patients with PD (24)(25)(26)(27). The Gba D409V/D409V mice present several distinct features of synucleinopathies, including cognitive impairment and pathogenic accumulation of α-synuclein, ubiquitin, and tau aggregates (21,22).…”
Section: Gz667161 Ameliorates Cognitive Impairment In the Gba-relatedmentioning
confidence: 99%
“…Mutations in GBA are now recognized as an independent risk factor for development of cognitive impairment in patients with PD (24)(25)(26)(27). The Gba D409V/D409V mice present several distinct features of synucleinopathies, including cognitive impairment and pathogenic accumulation of α-synuclein, ubiquitin, and tau aggregates (21,22).…”
Section: Gz667161 Ameliorates Cognitive Impairment In the Gba-relatedmentioning
confidence: 99%
“…Heterozygotes have a 10-30% chance of developing PD by age 80, which constitutes a 20-fold increase compared to non-carriers [7][8][9][10], and approximately 5-25% of "idiopathic" PD patients carry GBA mutations, making GBA mutations the greatest risk factor for PD discovered to date [11,12].…”
Section: G O'regan Et Al / Gba In Parkinson Diseasementioning
confidence: 99%
“…Several studies assessed the difference in cognitive performance between PD patients with and without GBA mutations [10,55,58,[61][62][63][65][66][67][68][69][70]; according to a recent meta-analysis, the risk of cognitive impairment is estimated to be 3 times higher for patients with GBA mutations [49]. However, significant differences in cognitive function between PD patients with and without GBA mutations were not confirmed in some studies [13,62,71,72].…”
Section: Non Motor Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of GBA1 mutation in subjects with mixed pathology of LB-type and AD-type was in between that of pure LB and pure AD subjects, suggesting a strong association between GBA1 mutation and LB-type neuropathological changes. Another study suggested that GBA1 mutation status might be an independent risk factor for cognitive impairment in patients with PD (Alcalay et al , 2012 ) (also see below for the relationship between GBA1 mutation and LB pathology).…”
Section: Gba1 Mutations In Parkinson ' S Diseasementioning
confidence: 99%